Transportation Asset Valuation: Pre-, Peri- and Post-Fourth Industrial Revolution. Issue 12 (December 2019) - Amekudzi-Kennedy, Adjo; Labi, Samuel; Singh, Prerna
A critical component of transportation asset management, asset valuation has been applied historically largely to provide condition-based value assessments of transportation infrastructure. There are emerging opportunities for innovations in asset valuation methodology with applications in the MAP-21/FAST performance-based era, and the Fourth Industrial Revolution (4IR). Opportunities exist to incorporate a wider range of value factors to capture multiple objectives in planning, design, and rehabilitation, such as safety, mobility, economic advancement, resilience, sustainability, and equity, to reflect the growing importance of intangible assets, as well as consider more explicitly value-adding technologies in this era of smarter infrastructure and rapid technological change. The paper first examines existing methods in transportation asset valuation practice and trends in asset valuation thinking through a literature review on asset valuation methodology with transportation applications. It then outlines innovation pathways and future research directions in asset valuation that can enhance existing capabilities to capture an expanding notion of transportation infrastructure value in the 21st century. For transportation professionals with continuing interest in valuation approaches to enhance asset management, this paper offers a catalog for identifying appropriate valuation approaches. For researchers and practitioners interested in pursuing innovations to secure increasingly smart, effective, and efficient transportation systems, the paper outlines innovation pathways and research directions enabled by growing computing power and data collection capabilities in the 4IR.